Chlamydia trachomatis Persistence in the Female Mouse Genital Tract: Inducible Nitric Oxide Synthase and Infection Outcome - Ramsey, Kyle H. (American Society for Microbiology, 2001)
It was previously reported that female mice resolve a primary Chlamydia trachomatis urogenital infection independent of inducible nitric oxide synthase (iNOS). We now report that although iNOS-deficient (NOS2(−/−)) mice resolve culture-apparent infection in a fashion similar to that of normal control (NOS2(+/+)) mice, they sustain significantly increased rates of disease, as assessed by hydrosalpinx formation. PCR amplification of ompA followed by Southern blot detection of amplicands revealed the presence of chlamydial DNA in the lower genital tracts of both NOS2(−/−) and NOS2(+/+) mice at ≥120 days postinfection and in upper genital tract tissues at >120 days postinfection. However, only NOS2(−/−) mice shed low numbers of viable chlamydiae from the lower genital tract after immunosuppressive treatment at 120 days postinfection. When cultured primary murine lung fibroblasts were activated in the presence of gamma interferon (IFN-γ), inhibition of chlamydial growth occurred in both NOS2(+/+) and NOS2(−/−) cells, but the inhibition was reversible after removal of the cytokine in the NOS2(−/−) primary cell culture only. The iNOS-independent inhibition was microbistatic but was independent of 2,3-indoleamine dioxygenase activity. We conclude that chlamydial DNA and antigens persist in mice subsequent to culture-apparent resolution. In addition, IFN-γ induces in vivo inhibition of chlamydial growth through microbistatic mechanisms in the absence of iNOS activity, but in the presence of iNOS activity, IFN-γ is microbicidal and effects eradication.